Glycan dependent phenotype differences of HIV-1 generated from macrophage versus CD4+ T helper cell populations - Heeregrave, Edwin J.; Thomas, Jordan; van Capel, Toni M.; de Jong, Esther C.; Pollakis, Georgios; Paxton, William A. (Frontiers in Immunology, 2023)
Generation of human immunodeficiency virus type 1 (HIV-1) stocks from different cell types can influence numerous virus phenotypes, including infectivity, co-receptor usage and neutralisation sensitivity. This can be due to incorporation of variant cell-specific molecules or differences in post-translational modifications of the gp41/120 envelope. In this study we produced genetically identical virus strains from macrophages, CD4-enriched lymphocytes as well as Th1 and Th2 CD4+ cell lines. All produced virus stocks were shown to be homogenous based on gp120 envelope sequencing. By normalization on infectivity we studied the effect of the producer host cell on various phenotypic aspects of the virus. Virus production by Th1 or Th2 cells did not compromise infectivity of the variant cell types tested. We observed no difference in sensitivity to co-receptor blocking agents upon viral passage through Th1 and Th2 CD4+ cell lineages nor did this affect DC-SIGN-mediated viral capture as measured in a transfer assay to CD4+ lymphocytes. Virus produced by macrophages was comparably sensitive to CC-chemokine inhibition as was virus generated from the array of CD4+ lymphocytes. We identified that virus produced from macrophages was fourteen times more resistant to 2G12 neutralisation than virus produced from CD4+ lymphocytes. Macrophage-produced dual-tropic (R5/X4) virus was six times more efficiently transmitted to CD4+ cells than lymphocyte-derived HIV-1 (p<0.0001) after DC-SIGN capture. These results provide further insights to what extent the host cell influences viral phenotype and thereby various aspects of HIV-1 pathogenesis but suggest that viruses generated from Th1 versus Th2 cells are consistent in phenotype.